Economic Returns to Speaking the Right Languages)? Evidence from Kazakhstan's Shift in State Language and Language of Instruction - Alisher Aldashev; Alexander M. Danzer (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper investigates the economic returns to language skills and bilingualism. The analysis is staged in Kazakhstan, a multi-ethnic country with complex ethnic settlement patterns that has switched its official state language from Russian to Kazakh. Using two newly assembled data sets, we find negative returns to speaking Kazakh and a negative effect of bilingualism on earnings while Russian was the official state language in the 1990s. Surprisingly, the Kazakh language continues to yield a negative wage premium 13 years after it has been made official state language. While we do neither find evidence for an ethnically segmented labor market nor for reverse causality, the low economic value of the Kazakh language can be explained by the comparatively poor quality of schools with Kazakh as language of instruction. Based on PISA data, we illustrate that scholastic achievements are substantially lower for pupils taught in Kazakh, despite the official support for the titular language. Our results suggest that switching the official state language without appropriate investments in school resources is unlikely to cure the economic disadvantage of a previously marginalized language.
Keywords: J24; I21; P23; O15; 330; Bilingualism; returns to language skills; wage premium; language policy; language of instruction